The Chinese economic experience - Yu-Hsuan, Wu (My University, 2011)
The main aim of this thesis is to assess the aspects that are in favour of China's successful development. The factors that have contributed to this include its unique socio-historical context, how it marries its domestic circumstances with the global market reality, as well as the implementation of the Chinese government's domestic, "non-economic" policies. Also, if China is considered a successful developing state it is necessary to examine critically how and which of its many aspects are conducive to economic development. Overall this thesis aims to provide an objective point of view of the topic in question, especially as viewpoints of China on other topics besides development, are often overly positive or negative.